Complex networks : structure, robustness, and function - Cohen, Reuven (Cambridge University Press, 2010)
"Examining important results and analytical techniques, this graduate-level textbook is a step-by-step presentation of the structure and function of complex networks. From the stability of the Internet to efficient methods of immunizing populations, from the spread of epidemics to how to search efficiently for individuals, this textbook explains the theoretical methods used, and the experimental and analytical results obtained. Ideal for graduate students entering this field, it gives detailed derivations of many results in complex networks theory. End-of-chapter review questions help students monitor their understanding of the materials presented"--